Identification and Analysis of Factors Contributing to Senior High School Students' Lack of Interest in Learning Physics: A Structural Equation Modeling - winda afriani Desmaniza; Pakhrur Razi; Desnita Desnita; Dea Stivani Suherman (Journal of Innovative Physics Teaching, 2026)
Interest in learning physics plays an important role in students’ academic success and their motivation to pursue further education in science-related fields. However, many senior high school students still show low engagement in physics learning, making it necessary to examine the factors that influence this condition. This study aimed to analyze the effects of internal and external factors on students’ interest in physics and their intention to continue higher education in physics-related disciplines. A quantitative research design was applied using the PLS-SEM approach. The participants consisted of 300 eleventh-grade science students from various senior high schools and Islamic senior high schools in West Sumatra, Indonesia, selected through proportionate stratified random sampling. Data were collected using a validated five-point Likert-scale questionnaire with good reliability and analyzed using SmartPLS4.0. The results showed that both internal and external factors significantly influenced students’ interest in physics, with external factors having a stronger effect. In addition, students’ interest significantly affected their intention to pursue higher education in physics-related fields. The model demonstrated strong explanatory power with R² values of 0.852 for interest and 0.804 for intention. These findings highlight the importance of supportive learning environments, effective teaching strategies, and self-efficacy in improving physics learning interest.